An investigation into the factors associated with pregnancy-associated glycoproteins in milk in seasonal-calving, pasture-based dairy cows - R.C. Doyle; M.M. Herlihy; J. Kenneally; M.C. Lucy; S.T. Butler (Journal of Dairy Science)
ABSTRACT: Pregnancy-associated glycoproteins (PAG) are secreted by trophoblast giant cells, and are detectable in blood and milk within the first month of gestation. The PAG concentration in blood and milk is believed to be 1 indicator of placental function and predictive of pregnancy maintenance. The objective of this retrospective study was to investigate factors associated with milk PAG sample minus the negative control mean optical density (S-N) profiles in cows managed under a seasonal-calving, pasture-based production system. Spring-calving dairy cows (n = 496) located in 3 Teagasc Research Farms in Ireland were enrolled in the study. Milk samples were collected weekly from each cow from wk 5 to 21 after artificial insemination (AI) to determine milk PAG S-N values. Body condition score was measured every 2 wk on a scale of 1 to 5 with 0.25 increments. Only cows that conceived to first AI and maintained pregnancy were retained for the final analysis (n = 247). Mixed models were used to evaluate the fixed effects of week after AI, BCS, dam fertility index (FI) and milk index, milk yield category, sire, parity, calf gender and calf birthweight on weekly milk PAG S-N profile, initial peak PAG, nadir PAG, and postnadir recovery peak PAG. Week after AI was associated with milk PAG S-N values, with mean week (and 95% CI) of initial peak values observed on week 6.4 (6.2, 6.5) after AI, nadir values on week 8.6 (8.55, 8.90) after AI, followed by recovery thereafter. We observed associations between parity, dam FI, milk yield, sire of the gestating embryo/fetus, fetal gender, and full-term calf birthweight with different aspects of the PAG S-N profile. Cows with the greatest FI had greater milk PAG S-N values at wk 5 and 6 after AI compared with cows with intermediate FI and least FI. There was also an association with parity because parity 1 cows had greater milk PAG S-N values than parity 2 and parity 3 cows during the initial peak and nadir stages of the PAG profile. An effect of sire on nadir milk PAG S-N values was observed, with PAG S-N values ranging from 0.5 to 1.2 between sires. In summary, milk PAG concentrations were associated with dam genetic merit, phenotypic milk production, and fetal characteristics. Assuming a correlation between milk PAG S-N values and placental function, these data provide evidence for an effect of genetic selection for fertility traits on placental development or function, or both.